2016
DOI: 10.1108/et-02-2016-0036
|View full text |Cite
|
Sign up to set email alerts
|

Commitment to an entrepreneurship training programme for self-employed entrepreneurs, and learning from participation

Abstract: Purpose The purpose of the article is to explore how self-employed entrepreneurs commit themselves to an entrepreneurship training programme and how such commitment relates to their perceptions of learning. Design/methodology/approach The data were collected through qualitative, inductive methods by interviewing and observing six entrepreneurs who took part in an entrepreneurship training programme. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…This debate has inspired contemporary programs in entrepreneurship education to include action-oriented, experiential, and transformative learning experiences situated in real entrepreneurial practices (Donnellon et al, 2014;Lackéus and Williams Middleton, 2015;Rasmussen and Sørheim, 2006). Few studies have, however, applied the situated learning perspective (Lave and Wenger, 1991) to understand entrepreneurial learning in education and training (Howorth et al, 2012;Kubberød and Pettersen, 2017;Nieminen and Hytti, 2016;Rae, 2003;Zhang and Hamilton, 2010), and in particular how this perspective can enrich our understanding of students' learning transformation in practice-based learning.…”
Section: Introductionmentioning
confidence: 99%
“…This debate has inspired contemporary programs in entrepreneurship education to include action-oriented, experiential, and transformative learning experiences situated in real entrepreneurial practices (Donnellon et al, 2014;Lackéus and Williams Middleton, 2015;Rasmussen and Sørheim, 2006). Few studies have, however, applied the situated learning perspective (Lave and Wenger, 1991) to understand entrepreneurial learning in education and training (Howorth et al, 2012;Kubberød and Pettersen, 2017;Nieminen and Hytti, 2016;Rae, 2003;Zhang and Hamilton, 2010), and in particular how this perspective can enrich our understanding of students' learning transformation in practice-based learning.…”
Section: Introductionmentioning
confidence: 99%
“…Saeed et al (2015) explored that university support in terms of education, concept development and business development can develop students' entrepreneurial intentions and motivate them to start a new business. Besides, a number of researchers confirmed that entrepreneurship education and training programmes of universities are also the ways of developing entrepreneurship (Iglesias-Sánchez et al , 2016; Nieminen and Hytti, 2016).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Kuratko (2003) claims that entrepreneurs can be taught by business practitioners and this can indeed yield meaningful results if carried out effectively. With traditional approaches to enterprise support training, coaching, mentoring and peer support are generally viewed as the central means of delivering entrepreneurial learning (Westhead and Storey, 1996;Nieminen and Hytti, 2016). However this requires the learning intervention to be correctly focused and the entrepreneur themselves to be open to the discovery process which entrepreneurial learning offers (Rae, 2000).…”
Section: Literature Review 21 Entrepreneurship and Icmentioning
confidence: 99%